(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
Middle school children are at a crucial turning point in their lives because they are becoming adolescents. Their brain is rapidly changing and pruning away unused connections. Because the brain loses neurons during adolescence, enhancing science curriculum through the arts is particularly important for cognitive development. The arts exercise certain areas of the brain that are used for learning. Research shows that children learn thinking skills through the arts that help them to be successful in eighth grade science. The arts enhance science curriculum through creative activities that promote thinking skills such as focusing, organizing, analyzing, interpreting, evaluating and reasoning. These skills help children develop higher levels of thinking and they help children to learn and understand eighth grade science.